The Impact of Modern Lifestyle on Circadian Rhythms - Radosław Zaucha; Stanisław Anczyk; Julia Silldorff; Marcin Dudek; Magdalena Gajkiewicz; Małgorzata Zając; Tomasz Fura; Oliwia Iszczuk; Zuzanna Felińska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Circadian rhythms are internal processes that regulate the sleep-wake cycle and repeat roughly every 24 hours. These rhythms are driven by a biological clock, primarily located in the suprachiasmatic nucleus (SCN) of the brain. Synchronized with environmental cues such as light and darkness, they play a crucial role in regulating sleep-wake patterns, hormone secretion, metabolism, and other physiological functions. Disruptions in circadian rhythms can have wide-ranging effects on health. This review aims to synthesize the current state of knowledge on how lifestyle factors affect circadian rhythms and explore the subsequent implications for both mental and physical health. Description of the state of knowledge: Modern lifestyles factors characterized by artificial lighting, shift work, noise pollution, excessive caffeine use, worldwide traveling and irregular eating habits can significantly disrupt natural circadian rhythms. Such disruptions are associated with a spectrum of pathologies, such as sleep dysregulation, mood disorders (e.g., depression and bipolar disorder), metabolic impairments, and suboptimal immune responses. Summary: This review synthesizes current research findings on the impacts of lifestyle-induced circadian misalignment, highlighting the complex interactions between modern life and circadian biology. Maintaining circadian rhythm integrity is crucial not just for enhancing overall well-being but also as a preventive strategy against a wide range of diseases. Integrating this understanding into health practices is essential for addressing the pervasive impact of circadian disruptions in modern society.